Egg Consumption and Human Health - Maria Luz Fernandez (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The purpose of this Special Issue, "Egg Consumption and Human Health," is two-fold: 1) to address the lack of effect of eggs in increasing heart disease risk (this discussion will be based on what is known from epidemiological analysis and clinical interventions) and 2) to focus on the role of eggs in protecting against chronic disease. Eggs are more than just a cholesterol-containing food. They possess numerous nutritional benefits. This Special Issue will discuss eggs as a source of high-quality protein for individuals across the life spectrum, as a substantial source of choline (a known neurotransmitter involved in cognitive function), and as a source of highly bioavailable lutein and zeaxanthin (two carotenoids well-recognized for their major role in protecting against age-related macular degeneration and cataracts, as well as for their antioxidant and anti-inflammatory properties). Finally, the potential of incorporating eggs for weight loss interventions, due to their low glycemic index and their satiety effects, will also be discussed.